"First with the most" Forrest - Henry, Robert Selph 1889-1970 (Konecky&Konecky, 1992)
This is an excellent older biography of Nathan Bedford Forrest. Henry used the Official Records extensively and gathered information from a number of sources to put together a biography that is favorable to Forrest but not worshipful and very entertaining to read.